2016
DOI: 10.2495/hpsm160391
|View full text |Cite
|
Sign up to set email alerts
|

Digital fabrication strategies for timber thin-walled sections

Abstract: A rise in digital fabrication technologies has led to numerous recent advances in the design and manufacture of woodworking joints. Computational generative processes can be used to create a part with integral mechanical attachments for friction-fit, adhesion-less connections between parts. These processes can additionally create machine code for production of such parts on computernumerically controlled (CNC) cutters. This paper investigates such computational processes for digital design and manufacture of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The volume transported is no longer minimized, but larger elements can be produced without discontinuities. For the mechanical performance, recent research on wood-wood connections for timber plate structures has shown the potential for standard building elements like walls with flat or curved geometries [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The volume transported is no longer minimized, but larger elements can be produced without discontinuities. For the mechanical performance, recent research on wood-wood connections for timber plate structures has shown the potential for standard building elements like walls with flat or curved geometries [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This can be partially abated through a fine control of part tolerance to achieve a friction-only fit (Robeller, 2015), or through interlocking geometry which prevents the movement of two parts in all but one direction (Robeller & Weinand, 2016), but such measures can also offset the ease of assembly. In terms of structural capacity, press-fit structures can possess compressive capacity approaching that of the glued sections, but can also be subject to a catastrophic 'pop-off' failure mechanism where sudden loss of friction cohesion causes an explosive bifurcation and complete disassembly (Al-Qaryouti et al, 2016).…”
Section: Press-fit Constructionmentioning
confidence: 99%
“…Notch, tab, and slot joint details are shown in Figure 4.3. Connection tolerance is known to have a strong effect on mechanical performance of digitally-fabricated joints (Al-Qaryouti, Gattas, Shi, & McCann, 2016;Robeller, 2015;Stitic, Robeller, & Weinand, 2018), and so final joint dimensions were found following a calibration study being undertaken on the CNC machines. HFT core joints were manufactured and calibrated by on a Nexus Water Line CNC waterjet cutting machine with a kerf diameter of 0.8mm.…”
Section: Connection Parametric Design and Tolerance Studymentioning
confidence: 99%